Validity of the Deed of the General Meeting of Shareholders regarding the Dismissal of Directors Without Notice and Absence - Izzah , Nurul; Djaja, Benny (Dinasti Research, 2024)
This article is entitled the validity of the deed of the general meeting of shareholders regarding the dismissal of directors without notice and absenteeism, legal research methods with normative research types, using the statute approach and conceptual research approaches . The secondary data sources use primary legal materials in the form of regulations that are relevant to legal issues, and secondary legal materials which are opinions and legal theories that are relevant to the legal issues in this writing. So with this analysis, it can be concluded that the validity of the deed of the general meeting of shareholders regarding the dismissal of directors without notification and absence from the agenda of the GMS meeting that is, it is invalid, because according to the Company Law the decision cannot be taken by the GMS, if the director who will be dismissed is not present because he has not been notified of the meeting regarding his dismissal. However, the GMS deed becomes valid upon the dismissal of a director who is not present at the GMS meeting, if the director has been notified regarding his dismissal at the GMS meeting and he refuses not to attend.